Association between individual occupational noise exposure and overweight/obesity among automotive manufacturing workers in South China - Jiaheng Yu; Jiaxin CUI; Haijuan Huang; Jingwen Zhang; Xin Li; Yanmei Ruan; Zejin Ou; Zhi Wang (BMC Public Health)
Abstract Background Occupational noise has been associated with numerous adverse health outcomes. However, limited evidence exists regarding its association with obesity. We aim to investigate the effect of occupational noise exposure on the risk of overweight/obesity among workers, providing scientific evidence for the prevention and management of overweight/obesity in the occupational population. Methods This study included 3427 participants from two factories in Guangzhou, China. Individual occupational noise exposure levels were assessed using cumulative noise exposure (CNE). Body mass index (BMI) data were obtained from physical examinations. Linear and logistic regression models, restricted cubic spline, as well as subgroup analyses, were used to explore the association. Results In continuous models, each 1 dB-year increase in CNE was significantly associated with a 0.03 (95% confidence interval (CI): 0.00, 0.05) kg/m² increase in BMI. In categorical models, higher CNE levels were significantly associated with BMI (β = 0.54, 95% CI: 0.16, 0.92) and overweight/obesity (odd ratio (OR) = 1.57, 95%CI: 1.21, 2.04). Restricted cubic splines (RCS) analysis demonstrated a linear dose-response relationship between CNE and overweight/obesity (P for overall=0.013, P for non-linear=0.175). Additionally, shift and night work were identified as critical moderating factors, with a stronger association observed among workers engaged in shift and night work. Conclusion Occupational noise exposure is positively associated with overweight/obesity, particularly among those engaged in shift and night work. Thus, enhancing noise source management and promoting awareness among workers for prevention are imperative.